Addressing the role of structured extensive listening among low-proficiency Thai learners of English - Jantasode, Chonlathorn; Ruangjaroon, Sugunya (Studies in English Language and Education, 2025)
Despite growing research on extensive listening (EL), structured approaches tailored for low-proficiency EFL learners struggling with self-directed learning are limited. The study examined 1) the effects of EL on students listening comprehension, 2) the correlation between EL hours and listening comprehension scores, and 3) student perceptions of the EL program. An embedded experimental design was employed in this research. A total of 66 students in the subsidized university in Thailand were selected using a purposive sampling technique. They were assigned to two groups33 students in the EL treatment group and the other 33 in the comparison group, which received classroom listening activities in the form of textbook-based listening exercises. The research instruments include a placement test, pre- and post-listening comprehension test, a listening log, and a focus-group interview. To analyze the data, t-tests were used to compare the groups and assess pre- and post-test improvements within the experimental group. Cohens d was calculated to determine the effect size of the improvement. Pearson correlation was used to evaluate the relationship between extensive listening hours and post-test scores, while the focus-group interview transcripts were analyzed using thematic analysis to examine students perceptions. The findings revealed a significant improvement in listening comprehension for the experimental group, with a moderate effect size. A positive correlation (r = .79) was found between listening hours and test scores. Qualitative findings revealed that students experienced greater enjoyment, confidence, motivation, and reduced anxiety compared to traditional classrooms, although some expressed concerns about the complexity of the listening logs. Overall, structured EL proves efficacy in enhancing listening comprehension and engagement for low-proficiency EFL learners.